Study of vacancies and Pd atom decoration on the electronic properties of bilayer graphene - Galván, Donald H.; Posada Amarillas, A.; Núñez González, R.; Mejía Rosales, Sergio; Yacamán, Miguel José (2010)
Abstract We have investigated the scenario of graphene when irradiated with high energetic protons and subsequently decorated with Pd atoms on one of the layers. Theoretical analyses were performed on graphene 2L (two layers) with vacancies (carbon 3 and 13) (sample A), graphene 2L with vacancies and the two carbon atoms intercalated in between the two carbon layers (sample B), graphene 2L with the vacancies intercalated and subsequently with two Pd atoms on one of the layers, the top layer (called surface) (sample C), and, last but not least, graphene 2L with vacancies intercalated and decorated with six Pd atoms on the surface (sample D). For the four cases enunciated, energy bands were performed which provided information about the semimetallic behavior, showing more semi-metallic character for the first case, while less metallic behavior occurs for the second and third one. Moreover, sample D showed a mini gap (between the conduction and valence bands) of the order of 0.02 eV and manifest semiconductor behavior. Total and projected density of states were performed in order to provide information about the contributions from each selected atom to the total DOS in the vicinity of the Fermi level in order to analyze the effect on the electronic behavior. Pd d orbitals contribute with ∼6% to the total DOS, while graphene (carbon atoms) p orbitals contribute with ∼5%. Furthermore, a strong hybridization is manifest between these two multiple degenerate orbitals. In addition, Crystal Orbital Overlap Population (COOP) between metal (M–M) contributions were calculated in order to inquire the existence (or absence) of magnetic instabilities. Pd atoms showed an itinerant ferromagnetic behavior which induces it to the graphene 2L samples.